2010
DOI: 10.4039/n09-074
|View full text |Cite
|
Sign up to set email alerts
|

Host-tree-related differences in trap captures and electroantennogram activity of Conotrachelus nenuphar (Coleoptera: Curculionidae)

Abstract: The plum curculio, Conotrachelus nenuphar (Herbst), is a serious pest of stone and pome fruits (Rosaceae) in eastern North America. We recorded captures of adult plum curculios in the field and measured electroantennogram (EAG) activity in the laboratory associated with cultivars of four hosts, 'Formosa' Japanese plum (Prunus salicina Lindl.), 'Stanley' European plum (P. domestica L.), 'Empire' apple (Malus domestica Borkh.), and 'Loring' peach (P. persica (L.) Batsch) (Rosaceae) to determine whether hosts tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Each of the synthetic volatiles was evaluated at Þve concentrations: 10.0, 1.0, 0.1, 0.01, and 0.001 mg/ml, diluted in DCM. The ÔStanleyÕ plum standard, found to be highly stimulating in previous studies, was produced according to the protocol described in Leskey et al (2010). Brießy, a large polyethylene bag (48.26 by 58.42 cm, Reynolds Oven Bags, Richmond, VA) was used as a source containment device; bags were placed over four selected ÔStanleyÕ plum branches of equal volume (i.e., similar size, architecture, and abundance of plant tissue).…”
Section: Methodsmentioning
confidence: 99%
“…Each of the synthetic volatiles was evaluated at Þve concentrations: 10.0, 1.0, 0.1, 0.01, and 0.001 mg/ml, diluted in DCM. The ÔStanleyÕ plum standard, found to be highly stimulating in previous studies, was produced according to the protocol described in Leskey et al (2010). Brießy, a large polyethylene bag (48.26 by 58.42 cm, Reynolds Oven Bags, Richmond, VA) was used as a source containment device; bags were placed over four selected ÔStanleyÕ plum branches of equal volume (i.e., similar size, architecture, and abundance of plant tissue).…”
Section: Methodsmentioning
confidence: 99%
“…Trials with multivoltine curculios were taken from a laboratory population established at the Appalachian Fruit Research Station (Kearneysville, West Virginia, United States of America) in 2001 and augmented annually with wild individuals, as per Leskey et al (2010). Adults were reared in the laboratory at 25 ± 2°C, 14:10 hour light:dark photoperiod on a diet of green thinning apples and water based on the methods of Amis and Snow (1985).…”
Section: Bioassaysmentioning
confidence: 99%
“…Multivoltine PCs used in EAG trials were treated as described above (bioassays) (Leskey et al 2010). Test subjects were fed, sexually mature females aged 14-21 days, since sexually mature females are considered to be the most damaging portion of the population and give statistically higher EAG responses compared to males (Leskey et al 2009(Leskey et al , 2010. There were four replicates per female, with seven females in the high dose modality, and six females for the low dose modality and also for the trials comparing GA.…”
Section: Electroantennogram Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive EAG signals have been reported many times in olfactory EAGs (Contreras et al, 1989;Haddad et al, 2010;Leskey et al, 2010;Light et al, 1988;Ramachandran et al, 1990;Schneider, 1957) and were hypothesized to be evoked by repellent compounds (Contreras et al, 1989). However, Leskey et al (2010) reported that the odor of preferred fruits evoked a positive signal in plum curculios (Conotrachelus nenuphar, Coleoptera), and Knaden et al (2012) postulated for Drosophila melanogaster that no reliable information about attractiveness or repellence was encoded in the neural signal before it reached the output neurons of the antennal lobe. We also found no preferences for either apple or almond pollen in a feeding experiment with B. terrestris (Ruedenauer et al, 2016).…”
Section: Pollen Of Different Plant Species Induces Different Eag Respmentioning
confidence: 99%